1992
DOI: 10.1042/bj2880297
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous presence of two distinct endoplasmic-reticulum-type calcium-pump isoforms in human cells. Characterization by radio-immunoblotting and inhibition by 2,5-di-(t-butyl)-1,4-benzohydroquinone

Abstract: Phosphorylation, immunoblotting, limited proteolysis and drug-sensitivity analysis were used to characterize the sarcoendoplasmic-reticulum Ca2+ ATPases in a variety of human cell types. In platelets, several megakaryoblastoid and lymphoblastoid cell lines two distinct autophosphorylated forms of these ATPases with molecular mass of 100 and 97 kDa could be observed, whereas in several other cell types the 97 kDa form was absent. On immunoblots the 97 kDa species was specifically recognized by an inhibitory mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 47 publications
6
72
0
Order By: Relevance
“…It is tempting to speculate that their reduced expression during differentiation reflects selective atrophy of this subcompartment that may account for at least part of the reduced total cell Ca 2ϩ content that we observed. In support of this possibility is evidence that the SERCA2b and SERCA3b Ca 2ϩ transport proteins are associated with different functional pools of intracellular Ca 2ϩ stores, the SERCA3b pool being more sensitive to release by IP 3 (62,63). Therefore, it is possible that the differentiation-induced reduction of SERCA2b may be accompanied by a reduction in the size of its associated Ca 2ϩ pool.…”
Section: Fig 8 Immunoblot Analysis Of Selected Er and Cytosolic Promentioning
confidence: 56%
“…It is tempting to speculate that their reduced expression during differentiation reflects selective atrophy of this subcompartment that may account for at least part of the reduced total cell Ca 2ϩ content that we observed. In support of this possibility is evidence that the SERCA2b and SERCA3b Ca 2ϩ transport proteins are associated with different functional pools of intracellular Ca 2ϩ stores, the SERCA3b pool being more sensitive to release by IP 3 (62,63). Therefore, it is possible that the differentiation-induced reduction of SERCA2b may be accompanied by a reduction in the size of its associated Ca 2ϩ pool.…”
Section: Fig 8 Immunoblot Analysis Of Selected Er and Cytosolic Promentioning
confidence: 56%
“…The recent observation that NO inhibits the active Ca2+ uptake into platelet membrane vesicles led us to check whether it could also increase the cytosolic Ca2 + concentration, as the well-known inhibitors of the SERCA pumps do (Thastrup, 1987;Thastrup et al, 1990;Papp et al, 1992). A significant rise in [Ca2+] was indeed observed.…”
Section: Discussionmentioning
confidence: 99%
“…as specific inhibitors of the sarco/endoplasmic reticulum Ca2+-ATPases (SERCA pumps) (Papp et al, 1992). These compounds elevate cytosolic [Ca2+] by inhibiting Ca2+ reuptake into the dense tubular system (Thastrup, 1987;Thastrup et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The IID8 antibody recognizes the SERCA 2b isoform at 100 kDa, whereas the PLIM430 antibody, obtained by immunizing with purified platelet internal membrane preparations (19), reacts with a distinct, 97-kDa pump species, temporarily designed as SERCA PLIM430 (17,18). The biochemical characteristics and the intracellular localization of these two pump species are different (17)(18)(19)(20)(21), suggesting that they play functionally distinct roles within the same cell. To better elucidate the functional specialization of the coexpressed calcium pump isoforms, in the present work we investigated the modulation of the expression of these enzymes during in vitro lymphocyte activation, a process where significant changes of cell function, structure, and signaling occur.…”
mentioning
confidence: 99%
“…Previously, we have shown that in human cell lines of hemopoietic origin, isoform-specific anti-SERCA monoclonal antibodies can detect two distinct enzyme species that are coexpressed in the same cells (17,18). The IID8 antibody recognizes the SERCA 2b isoform at 100 kDa, whereas the PLIM430 antibody, obtained by immunizing with purified platelet internal membrane preparations (19), reacts with a distinct, 97-kDa pump species, temporarily designed as SERCA PLIM430 (17,18). The biochemical characteristics and the intracellular localization of these two pump species are different (17)(18)(19)(20)(21), suggesting that they play functionally distinct roles within the same cell.…”
mentioning
confidence: 99%